2008
DOI: 10.1017/s1461145708008559
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile stress-induced alteration of maturation of the GABAA receptor α subunit in the rat

Abstract: Profound evidence indicates that GABAA receptors are important in the control of physiological response to stress and anxiety. The alpha subunit type composition contributes significantly to the functional characterization of the GABAA receptors. The alpha2, alpha3, alpha5 subunits are predominately expressed in the brain during embryonic and early postnatal periods of normal rats, whilst alpha1 are most prominent during later developmental stages. In the present study, we examined the long-term effects of juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 54 publications
4
40
2
Order By: Relevance
“…The reduction of activity/exploration in novel environments has been interpreted as reflective of anhedonic-like behavior (Fukushiro et al, 2012). The lack of anxiogenic effects of the present model contrasts with other previous reports (Avital et al, 2006;Bazak et al, 2009;Ilin and Richter-Levin, 2009;Jacobson-Pick and Richter-Levin, 2012;Jacobson-Pick et al, 2008;Tsoory et al, 2007Tsoory et al, , 2010. Although this might suggest that our procedure is of lower intensity than previous protocols, this is difficult to demonstrate and not supported by the observed reduction of body weight gain.…”
Section: Accepted M Manuscriptcontrasting
confidence: 97%
See 1 more Smart Citation
“…The reduction of activity/exploration in novel environments has been interpreted as reflective of anhedonic-like behavior (Fukushiro et al, 2012). The lack of anxiogenic effects of the present model contrasts with other previous reports (Avital et al, 2006;Bazak et al, 2009;Ilin and Richter-Levin, 2009;Jacobson-Pick and Richter-Levin, 2012;Jacobson-Pick et al, 2008;Tsoory et al, 2007Tsoory et al, , 2010. Although this might suggest that our procedure is of lower intensity than previous protocols, this is difficult to demonstrate and not supported by the observed reduction of body weight gain.…”
Section: Accepted M Manuscriptcontrasting
confidence: 97%
“…This contrasts with previous reports of increased anxiety (Giovanoli et al, 2013;Jacobson-Pick et al, 2008;Maslova et al, 2002aMaslova et al, , 2002bTsoory et al, 2007;Yee et al, 2011), although negative or inconsistent results have also been reported (Avital and Richter-Levin, 2005;Bourke and Neigh, 2011;Jacobson-Pick and Richter-Levin, 2010;McCormick et al, 2007;Peleg-Raibstein and Feldon, 2011;Pohl et al, 2007;Toledo-Rodríguez and Sandi, 2007). This is likely related to a differential susceptibility to stress among the different strains of rats and mice used (e.g., Maslova et al, 2002aMaslova et al, , 2002b.…”
Section: Accepted M Manuscriptcontrasting
confidence: 87%
“…Given increased levels of GABA Aα2 mRNA in the amygdala are found in stressed animals (38), the reductions in GABA receptor subunits induced by the Lactobacillus suggest that this bacteria could have promoted an adaptive advantage over broth-fed animals in terms of interaction with stressful situations. The amygdala is also necessary for conditioning of a relatively simple stimulus or cue (conditioned stimulus) and the context in which the unconditioned stimulus is delivered (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…L. rhamnosus (JB-1) administration also affected the transcripts of GABA A receptor subunits in the hippocampus. Although differences in the expression of the transcript for GABA Aα2 and GABA Aα1 have been found in the hippocampus of rats subjected to different learning tasks, these changes are not consistent (38,42). Nevertheless, it has been shown that GABA A receptors bearing the GABA Aα2 subunit mediate the anxiolytic effects of benzodiazepines, whereas GABA A receptors that have the α1 subunit mediate the sedative and amnesic effects of benzodiazepines (12).…”
Section: Discussionmentioning
confidence: 99%
“…While most ELS rodent models focus on the perinatal to pre-weaning periods and involve some form of maternal deprivation or separation (for a review, see [25]), we have focused in recent years on an alternative period in the rat ontogeny, ‘juvenility’ (∼28 days), the earlier phase of the adolescent/post-weaning to pre-pubertal period [26,27,30,31,38,44,45,46,49,51,59] (for a summary of the main findings, see tables 1 and 2). …”
Section: Post-weaning To Pre-pubertal (Juvenile) Stress Modelmentioning
confidence: 99%